POTENSI PEMANFAATAN LUBANG RESAPAN BIOPORI DI KELURAHAN KOTA BAMBU SELATAN, PALMERAH, JAKARTA BARAT - Pramiati Purwaningrum; Winarni Winarni; Hernani Yulinawati; Tazkiaturrizki Tazkiaturrizki (Universitas Trisakti, 2021)
Biopore Infiltration Hole (LRB) is an alternative and simple technology for rainwater infiltration that can be useful as a processor for organic waste from households and can be applied in narrow urban residential areas such as in Kota Bambu Selatan (KBS) Sub-district. LRB technology in general is to reduce water inundation, increase groundwater reserves, and reduce the volume of organic waste. Therefore, the Community Service Program of the Environmental Engineering Study Program has the aim of providing counseling and training to PPSU officers (Public Facilities and Infrastructure Handling Workers) of KBS Sub-district in implementing LRB in accordance with technical requirements without impacting groundwater pollution. The method used was to provide LRB educational materials aimed at the community, especially PPSU officers through direct explanations, educational posters and brochures. The current condition is that KBS Sub-district already has LRB at several points in 2017, however it got some technical problems such as pipe size is too small, namely 7.5 cm (minimum pipe diameter requirement is 10 cm); there is dredging activity, there is no top cover so that small animals often enter, and in some locations there is often stagnant water.